Effect of Market Orientation on Channel Strategy- An Empirical Analysis of Pesticide Industry - Mobin ul Haque; Sarwar M. Azhar (Journal of Management and Research, 2014)
Research in market orientation has overlooked the importance of its impact on various aspects of marketing strategy, especially on distribution channel strategy. Using Kohli & Jaworski's framework of measuring market orientation (MO) and pesticide industry of Pakistan as a context, this article explores the relationship between various constructs of MO with channel strategy. This paper draws survey data from the pesticide industry in Pakistan. Given the low response rate, a norm in developing countries, boots trapping technique is employed and tests are run. The results reveal that level MO has an impact on how channel strategies are formulated. Findings of the research indicate that higher level of MO is associated with selective channel strategy involving low intensity of distribution and higher channel control. The results also suggest that the right channel strategy helps an organization to create differentiation and to improve performance in a commodity market.